A Post-mortem Survey of Bovine Female Reproductive Tracts in the UK - Millward, Sam; Mueller, Karin; Smith, Robert; Higgins, Helen M. (Frontiers in Veterinary Science, 2019)
The aim of this study was to estimate the prevalence of macroscopic reproductive tract abnormalities in a sample of female cattle in the UK. To our knowledge, this type of post-mortem survey has not been conducted in the UK since the 1970s. Over the last 40 years significant changes have occurred with respect to management and genetics. Moreover there have been changes in growth rates in beef animals, elevated milk yields and a decline in fertility in dairy cattle. It was hypothesized that differences may exist in the extent and type of lesions occurring compared with previous studies. Between May and July 2017, the reproductive tracts of cattle (Bos taurus) were examined post-mortem at an abattoir in the north west of England. All female cattle slaughtered on visit days were eligible. In total 680 tracts were examined, constituting 88% of those eligible. Macroscopic abnormalities were recorded using a standard format and definitions. The majority of cattle were a dairy breed (73%) with Holstein-Friesian accounting for over half of these. Median age at slaughter for dairy breeds was 5.1 years (range 1.7 – 13.8 years) and 3.9 years (0.92 -16.8 years) for beef breeds. A total of 141 out of the 680 reproductive tracts examined exhibited at least one lesion, giving an overall prevalence of abnormalities of 20.7%, with 95% confidence interval (CI) 17.9 - 23.9%. This is double the last similar UK-based study carried out in the late 1970s. There were 20 different types of abnormality identified, with 207 individual lesions in 141 abnormal tracts. The ovary was the most common anatomical location displaying abnormalities, accounting for 70.2% of all abnormal tracts. Ovaro-bursal adhesions were the most common abnormality found at 5.3% (CI 3.9-7.2%) and half of these were classified as severe. The second most common lesion was follicular cystic ovarian disease at 4.6% (CI 3.2 - 6.4%), followed by anoestrus at 4.1% (CI 2.9-5.9%). Double the prevalence of macroscopic reproductive tract lesions is a concern. Greater use of post-mortem material for disease surveillance and further studies into risk factors, especially for the most prevalent lesions, is warranted.